Peripheral serotonin: An unraveled metabolite in bovines - SRINIVAS, BANDLA (The Indian Journal of Animal Sciences, 2022)
Serotonin is an omnipotent molecule in the brain and rest of the body and plays a pivotal role in the gut-brain axis. Serotonin’s role in neurotransmission and its function at molecular levels with different genetic variants has been widely covered across the animal kingdom. Although the digestion process in ruminants is pillared on anaerobic microflora present in the rumen, the impact of the rumen microbial population on serotonergic activity is seldom explored. Besides its principal effect on the gastrointestine, it regulates the excretion of bile acids, glucose and lipid homeostasis, energy balance, immunomodulation, and various other vital processes in the animal system. However, the studies on part of peripheral serotonin are moderate and very few in bovines. The objective of this review is to appreciate research conducted on the basics of serotonin, triallelic polymorphism in SLR6A4 gene polymorphism, receptors and its role in GI, liver, pancreas, adipocytes, and to a little extent in other organs like uterus, mammary gland, etc. in different species and look forward to expanding the information in bovines.